Konsep Honne Tatemae Tokoh Utama dalam Anime Omoi Omoware Furi Furare - Haryanti Oktavia, Devi; Syihabuddin (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2024)
This study is a descriptive qualitative research with a phenomenological approach. The research delves into the concept of Honne-Tatemae used in communication in the anime